The EamA metabolite transporter does not affect antileishmanial drug susceptibility. - Ahmad, R.; Gastoldi, G.; Wong, S. T.; Baeza Garcia, A.; Caljon, G. (Int J Parasitol Drugs Drug Resist, 2026)
Leishmaniasis is a major neglected tropical disease, exists in 98 countries and constitutes a global public health threat. As chemotherapy is confronted with drug resistance and treatment failure, understanding the underlying mechanisms and continued drug discovery efforts are needed in the fight against leishmaniasis. A previous cosmid-based overexpression study suggested a role for EamA (LINF_020008400), annotated as a putative drug-metabolite transporter, in resistance to novel antileishmanial oxaboroles. To assess fitness cost and drug susceptibility, gene deficient Leishmania infantum lines were generated using CRISPR-Cas9 gene editing and overexpression from the ssu locus was achieved using the pLEXSY system. While in vitro parasite growth and survival were unchanged compared to control lines, the intracellular burden of the null mutant was lower. In vitro exposure to current antileishmanial drugs and several novel leads revealed an unchanged drug sensitivity profile in extracellular and intramacrophage assays. Similarly, the overexpression lines showed a significantly lower infection rate, but their drug susceptibility profiles showed no significant differences from the control. Collectively, these data suggest that -under the tested conditions- LINF_020008400 is not essential for parasite fitness, host cell infectivity and survival following exposure to antiparasitic drugs.
Keywords: *Antiprotozoal Agents/pharmacology; *Leishmania infantum/drug effects/genetics/metabolism; Drug Resistance; Animals; *Membrane Transport Proteins/genetics/metabolism; *Protozoan Proteins/genetics/metabolism; Humans; Macrophages/parasitology; CRISPR-Cas Systems; Gene Editing